The print media convergence: Overall trends and the COVID-19 pandemic impact - Marina Sheresheva; Lyudmila Skakovskaya; Elena Bryzgalova; Anton Antonov-Ovseenko; Helen Shitikova (Journal of Risk and Financial Management, 2021)
The study presented in the paper aims to analyze the Russian print media market before and during the COVID-19 pandemic, as well as the prospects of local media transformation in the challenging environment. In the pre-pandemic decade, there was a growing body of literature on media convergence in emerging markets confirming that this concept is growing in importance as a strategic path of conventional media transformation. Still, the research on the Russian conventional media transformation is scarce, the impact of the COVID-19 pandemic risks on Russian print media and their business models have not been investigated so far. To fill the gap, we combined desk research, processing of published industry statistics, and data obtained by means of expert interviews. The results confirm that in the first decades of the 21st century Russian print media paid less attention to the opportunities of media convergence than Western ones. At the same time, those Russian conventional media that set ambitious goals for their future considered the adoption of the media convergence approach as crucial, even before the pandemic. The findings show the lack of systemic measures to improve the overall situation on the national media market that faces difficult times, and the need to take into account pandemic risks in the print media management activities.
Keywords: 330; SARS-CoV-2; Russia; communication; coronavirus; digitalization; media convergence; print media